Affect Intensity and Lability: The Role of Posttraumatic Stress Disorder Symptoms in Borderline Personality Disorder - Marshall-Berenz, Erin C. (2011)
BACKGROUND: Emotion dysregulation is likely a core psychological process underlying the heterogeneity of presentations in borderline personality disorder (BPD) and is associated with BPD symptom severity. Emotion dysregulation has also been independently associated with posttraumatic stress disorder (PTSD), a disorder that has been found to co-occur with BPD in 30.2% of cases in a nationally representative sample. However, relatively little is known about the specific relationships between emotion dysregulation and PTSD among those diagnosed with BPD. The purpose of the current study was to evaluate relations between PTSD symptom severity and negative affect intensity and affective lability among individuals with BPD. METHOD: Participants were 67 individuals diagnosed with BPD (79% women; M(age) = 38, SD = 10), who reported one or more DSM-IV PTSD Criterion A events. RESULTS: Hierarchical multiple regression analyses indicated that when examined concurrently with BPD symptom severity, PTSD symptom severity, but not BPD symptom severity, was related to negative affect intensity and affective lability. Reexperiencing symptoms uniquely predicted affective lability, and hyperarousal symptoms uniquely predicted negative affect intensity, lending additional support to emerging literature linking reexperiencing and hyperarousal symptoms with emotion dysregulation. CONCLUSIONS: PTSD symptom severity among individuals with a BPD diagnosis is related to elevations in emotion dysregulation. It is important to evaluate whether early treatment of PTSD symptoms provided concurrently with BPD treatment leads to enhanced improvements in emotion regulation among individuals with co-occurring PTSD and BPD.